Helicobacter pylori infection increase the risk of subclinical hyperthyroidism in middle-aged and elderly women independent of dietary factors: Results from the Tianjin chronic low-grade systemic inflammation and health cohort study in China - Zhang, Juanjuan; Hai, Xinghua; Wang, Siyu; Zhu, Fan; Gu, Yeqing; Meng, Ge; Zhang, Qing; Liu, Li; Wu, Hongmei; Zhang, Shunming; Zhang, Tingjing; Wang, Xing; et al. (Frontiers in Nutrition, 2023)
Background: Prospective studies on the association between Helicobacter pylori (H. pylori) infection and subclinical hyperthyroidism are limited. We therefore designed a large-scale cohort study to explore the association between H. pylori infection and the risk of subclinical hyperthyroidism in women. Methods: This prospective cohort study investigated 2,713 participants. H. pylori infection was diagnosed with the carbon 13 breath test. Subclinical hyperthyroidism was defined as serum thyroid-stimulating hormone levels are low or undetectable but free thyroxine and tri-iodothyronine concentrations are normal. Propensity score matching (PSM) analyses and Cox proportional hazards regression models were used to estimate the association between H. pylori infection and subclinical hyperthyroidism. Results: 1025 PS-matched pairs of H. pylori infection women were generated after PSM. During 6-years of follow-up, the incidence rate of subclinical hyperthyroidism was 7.35/1000 person-years. After adjusting potential confounding factors (including iodine intake in food and three main dietary patterns score), the multivariable hazard ratio (HR) (95% confidence intervals) of subclinical hyperthyroidism by H. pylori infection were 2.49 (1.36, 4.56). Stratified analyses suggested a potential effect modification by age, the multivariable HR (95% confidence intervals) was 2.85 (1.45, 5.61) in age ≥ 40y participants and 0.70 (0.08, 6.00) in age < 40y participants (P for interaction =0.048). Conclusions: Our prospective study firstly indicates that H. pylori infection is significantly associated with the risk of subclinical hyperthyroidism independent of dietary factors among Chinese women, especially in middle-aged and older individuals.